2008
DOI: 10.1016/j.neuron.2008.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Deprivation Unmasks a PKA-Dependent Synaptic Plasticity Mechanism that Operates in Parallel with CaMKII

Abstract: Calcium/calmodulin kinase II (CaMKII) is required for LTP and experience-dependent potentiation in the barrel cortex. Here, we find that whisker deprivation increases LTP in the layer IV to II/III pathway and that PKA antagonists block the additional LTP. No LTP was seen in undeprived CaMKII-T286A mice, but whisker deprivation again unmasked PKA-sensitive LTP. Infusion of a PKA agonist potentiated EPSPs in deprived wild-types and deprived CaMKII-T286A point mutants but not in undeprived animals of either genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
59
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(66 citation statements)
references
References 49 publications
5
59
2
Order By: Relevance
“…LTP is partly NO-dependent in wild-type and entirely NO-dependent in GluR1 knockout mice (Hardingham and Fox, 2006) and LTP is known to interact with EDP in barrel cortex (Hardingham et al, 2008). Therefore, we tested whether αNOS1 was also involved in cortical LTP.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…LTP is partly NO-dependent in wild-type and entirely NO-dependent in GluR1 knockout mice (Hardingham and Fox, 2006) and LTP is known to interact with EDP in barrel cortex (Hardingham et al, 2008). Therefore, we tested whether αNOS1 was also involved in cortical LTP.…”
Section: Resultsmentioning
confidence: 99%
“…In wild-type mice, pairing pre- and post-synaptic action potentials so that the post-synaptic action potential occurs 10ms after the presynaptic action potential (Figure 4) produces significant potentiation of EPSPs in 37.5% of cases and causes an average EPSP potentiation of 29 ± 8% of control values (Hardingham et al, 2008). Previous studies have shown that GluR1 KOs also exhibit LTP in this pathway (Hardingham and Fox, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence that EDD in the barrel cortex is mechanistically similar to LTD comes from studies showing that both depend on the GluR1 subunit of the AMPA receptor in the somatosensory cortex [30] and the fact that LTD can be occluded by whisker deprivation patterns that cause EDD [5,6]. Crucially, EDD requires cortical activity [49], consistent with an anti-correlation mechanism of depression in barrel cortex [50].…”
Section: Discussionmentioning
confidence: 99%
“…In developing animals, LTD and experience-dependent depression (EDD) depend on cannabinoid signalling [11,12]. Further evidence comes from studies that show that experience-dependent plasticity interacts with synaptic plasticity in a way that might be predicted if one depended on the other: for example, in the barrel cortex EDD occludes LTD and enhances LTP [5,13,14]. …”
Section: Introductionmentioning
confidence: 99%
“…Molecular correlates of plasticity Studies describing the cellular mechanisms underlying experiencedependent plasticity in the barrel cortex system, typically by electrophysiological means, are plentiful (see e.g (Allen et al, 2003;Celikel et al, 2004;Cheetham et al, 2007;Chittajallu and Isaac, 2010;Finnerty et al, 1999;Fox, 1992;Greenhill et al, 2015;Hardingham et al, 2008;Harris and Woolsey, 1981;House et al, 2011;Kätzel and Miesenböck, 2014;Kossut, 1985;Lendvai et al, 2000;L. Li et al, 2009;P.…”
Section: )mentioning
confidence: 99%